Pengaruh Pembangunan Infrastruktur Terhadap Pertumbuhan Ekonomi di Indonesia - Putri, Pujria Rahma; Azhar, Zul (Universitas Negeri Padang, 2024)
In sustainable economic development, good infrastructure development is needed so that people's needs are met. Judging from the economic growth rate of GRDP at constant prices according to fluctuating expenditure. This study aims to identify the effect of infrastructure development on economic growth in Indonesia. With the Panel Least Squares (PLS) method then proceed with the classical assumption test, with a panel regression model. Research on 34 provinces in Indonesia with a span of 10 years. The results of the study show that road infrastructure has a negative and insignificant effect on economic growth in Indonesia. Electricity Infrastructure has a positive and significant effect on Economic Growth in Indonesia. Telephone Infrastructure has a positive and significant effect on Economic Growth in Indonesia. Clean Water Infrastructure has a positive and significant effect on Economic Growth in Indonesia. It can be concluded that infrastructure development is very important for the development of a country. From the results of this study it is suggested to the government to pay more attention to empowerment policies that can support this. so as to achieve economic growth.